2004
DOI: 10.1159/000075141
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of a ‘Minor’ Form of Brachmann-de Lange Syndrome by Three-Dimensional Sonography and Three-Dimensional Computed Tomography

Abstract: Brachmann-de Lange syndrome is a congenital disease characterized by severe mental retardation, pre- and postnatal symmetric growth delay, limb defects, visceral anomalies, hirsutism, and a typical face. The authors describe the prenatal sonographic pattern of Brachmann-de Lange syndrome suspected at 20 weeks of gestation, with severe intrauterine growth retardation, facial dysmorphism, cardiac abnormality, and micromelia without the typical defects of the upper limbs. Fetal karyotyping was normal. The diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…To the best of our knowledge, based on a MEDLINE search, there is only 1 previous report describing the use of 3D sonography in the evaluation of structural anomalies in a fetus with a minor form of Brachmann-de Lange syndrome. 8 In our case, the classic findings of the condition were present, which allowed correct diagnosis in the second trimester of pregnancy. Of note, long eyelashes, which is a characteristic feature present in 99% of affected infants 2 but has not been previously reported as a prenatal finding, was specifically sought and detected at 26 weeks and largely contributed to the prenatal diagnosis.…”
supporting
confidence: 50%
“…To the best of our knowledge, based on a MEDLINE search, there is only 1 previous report describing the use of 3D sonography in the evaluation of structural anomalies in a fetus with a minor form of Brachmann-de Lange syndrome. 8 In our case, the classic findings of the condition were present, which allowed correct diagnosis in the second trimester of pregnancy. Of note, long eyelashes, which is a characteristic feature present in 99% of affected infants 2 but has not been previously reported as a prenatal finding, was specifically sought and detected at 26 weeks and largely contributed to the prenatal diagnosis.…”
supporting
confidence: 50%
“…According to some authors, even hirsutism should be visible on ultrasound. 12,16 Our first case is a good example of minimal prenatal expression, in which the molecular test was crucial to validate the diagnosis. Even in the second case, if we ignore the congenital heart defect and the polydactyly that were actually missed, the baby presented initially only with late IUGR and facial dysmorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…18 Suspicious ultrasound findings are usually the identification of upper limb defects, often asymmetric and unilateral, the presence of a congenital diaphragmatic hernia, visceral anomalies, and symmetric intrauterine growth retardation (IUGR), which is present in 95% of cases and becomes more obvious after the 25th week of gestation. 16 Over time, published reports have added other ultrasonographic signs, such as an abnormal nuchal translucency. 14,19 Prenatal recognition of dysmorphic features became possible with the use of the latest generation of ultrasound equipment that enabled measurement of the precise morphometric parameters of the fetal face, but this technique requires specific and considerable experience.…”
mentioning
confidence: 99%
“…Sekimoto et al (2000) compared the prenatal findings in 10 reported cases of CdLS and reported IUGR, limb defects, diaphragmatic hernia and abnormal face to be the most frequent ultrasound findings. Le Vaillant et al (2004) reported on an overlapping series of patients and concluded very similar prenatal observations. In our cases micrognathia, limb abnormalities and late onset of IUGR were the findings suggestive of CdLS.…”
Section: Discussionmentioning
confidence: 56%